Advanced fibre-reinforced polymer (FRP) composites for structural applications (Woodhead Publishing series in civil and structural engineering ;, 2022)
Advanced Fibre-reinforced Polymer (FRP) Composites for Structural Applications, Second Edition provides updates on new research that has been carried out on the use of FRP composites for structural applications. These include the further development of advanced FRP composites materials that achieve lighter and stronger FRP composites, how to enhance FRP integrated behavior through matrix modification, along with information on pretension treatments and intelligence technology. The development of new technology such as automated manufacturing and processing of fiber-reinforced polymer (FRP) composites have played a significant role in optimizing fabrication processing and matrix formation. In this new edition, all chapters have been brought fully up-to-date to take on the key aspects mentioned above. The book's chapters cover all areas relevant to advanced FRP composites, from the material itself, its manufacturing, properties, testing and applications in structural and civil engineering. Applications span from civil engineering, to buildings and the energy industry.